Consumers’ Perceptions of the Assortment Offered in a Grocery Category: The Impact of Item Reduction - Broniarczyk, Susan M.; Hoyer, Wayne D.; McAlister, Leigh (Journal of Marketing Research, 1998)
Grocery retailers have been informed that, to remain competitive, they must reduce the number of stockkeeping units (SKUs) offered, in line with consumer demand, or, in other words, adopt “Efficient Assortment.” Retailers have resisted this principle on the basis of a fear that eliminating items would lower consumer assortment perceptions and decrease the likelihood of store choice. In two studies, the authors examine how consumers form assortment perceptions in the face of SKU reduction with a particular emphasis on two heuristic cues: the availability of a favorite product and the amount of shelf space devoted to the category. Results indicate that retailers might be able to make substantive reductions in the number of items carried without negatively affecting assortment perceptions and store choice, as long as only low-preference items are eliminated and category space is held constant. Thus, the potential risk inherent in item reduction might be more limited than initially thought. The authors then discuss the implications of these findings for retailers, as well as additional measurement considerations.